Transformasi Pondok Pesantren dalam Menanggulangi Radikalisme Agama Pada Pondok Pesantren Daerah Penyangga Ibu Kota Jakarta - Mundzier Suparta; Suhada Suhada; Taufik Abdillah Syukur (STAI ALHIKMAH Jakarta, 2018)
This article is about the transformation of Islamic boarding schools in tackling religious radicalism in Islamic boarding schools in the capital city of Jakarta. This article uses descriptive methods to obtain the whole picture of the problems found in the field. The unit of analysis used is The Leader or Pak Kyai, Teachers and Students, Santri. The findings in this article are: First, Transforming the purpose of Islamic boarding schools in overcoming religious radicalism in Islamic boarding schools in the capital city of Jakarta by trying to create and develop Muslim personalities who believe and worship unto Allah, good behavior & character and being useful for society. Islamic boarding schools guide students to become adult students, act and think critically and responsibly, also foster an attitude of mutual respect and appreciate for distinctive cultural, customs, race and every other person’s abilities. Second, the transformation of the Islamic boarding school curriculum in overcoming religious radicalism in Islamic boarding schools in the capital city of Jakarta by using a curriculum that teaches the science of comparative Mazhab, so not to give the impression of exclusivity from other thoughts. Third, Transformation of teaching methods in Islamic HIKMAH, Vol. XIV, No. 1, 2018 boarding schools to overcoming religious radicalism in Islamic boarding schools in Jakarta’s capital city by increasing the use of cooperative learning or teaching methods designed to educate group cooperation. Besides being developed to achieve academic learning achievements, the method is also effective in developing social skills and encourages respect for the opinions of others so that it becomes a way to overcome religious radicalism towards Santri. Keywords: Islamic Boarding School, Religius Radicalism Artikel ini mengenai transformasi pondok pesantren dalam menanggulangi radikalisme agama pada pondok pesantren daerah penyangga ibu kota Jakarta. Artikel ini menggunakan metode deskriptif untuk memperoleh gambaran secara keseluruhan permasalahan yang ditemukan di lapangan. Unit analisis yang digunakan adalah Pengasuh atau Kyai Pondok Pesantren, Guru dan Santri. Temuan dalam artikel ini adalah: Pertama, Transformasi tujuan pondok pesantren dalam menganggulangi radikalisme agama di pondok pesantren daerah penyangga ibu kota Jakarta yaitu dengan berusaha untuk menciptakan dan mengembangkan kepribadian muslim yang beriman dan bertaqwa kepada Allah Swt, berakhlak mulia dan bermanfaat bagi masyarakat. Pesantren membimbing santri agar menjadi santri dewasa, bertindak dan berpikir secara kritis dan bertanggung jawab, juga menumbuhkan sikap saling menghargai dan menghormati setiap perbedaan budaya, adat istiadat, ras dan setiap kemampuan orang lain. Kedua, Transformasi kurikulum pondok pesantren dalam menganggulangi radikalisme agama di pondok pesantren daerah penyangga ibu kota Jakarta dengan memasukkan kurikulum yang mengajarkan kepada ilmu perbandingan mazhab, sehingga tidak memberi kesan eksklusifisme dari pemikiran lain. Ketiga, Transformasi metode pengajaran pondok pesantren dalam menganggulangi radikalisme agama di pondok pesantren daerah penyangga ibu kota Jakarta dengan memperbanyak penggunaan pembelajaran kooperatif atau metode pengajaran yang dirancang untuk mendidik kerja sama kelompok. Di samping dikembangkan untuk mencapai prestasi hasil belajar akademik, metode itu juga efektif untuk mengembangkan keterampilan sosial serta mendorong untuk menghormati pendapat orang lain sehingga menjadi cara untuk menanggulangi radikalisme agama pada santri. Kata Kunci: Pondok Pesantren, Radikalisme Agama